2018
DOI: 10.22478/ufpb.1981-1268.2018v12n2.35991
|View full text |Cite
|
Sign up to set email alerts
|

Adaptação de um índice de integridade biótica para análise da sustentabilidade em florestas urbanas

Abstract: Diante da complexidade de monitorar, avaliar e planejar o manejo de fragmentos urbanos para garantir sua sustentabilidade, o uso de índices é um modo rápido de obtenção de dados relevantes, informações mensuráveis em campo e de parâmetros para realização de comparações e análises diagnósticas. O presente estudo teve por objetivo adaptar um índice de integridade biótica para uso em Floresta Estacional Semidecidual, bem como testar sua eficiência no diagnóstico da integridade biótica de fragmentos florestais ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 12 publications
0
9
0
6
Order By: Relevance
“…Among the environmental quality assessment methods, one finds the Index of Biotic Integrity (IBI) (MEDEIROS; TOREZAN, 2013), which uses environmental variables such as incidence of indicator species, forest structure, as well as incidence of gaps/dead trees, grass or exotic woody species. Therefore, one can assume that the greater the biotic integrity of a given fragment, the greater its resilience (GRACIANO-SILVA; MELLO; CARDOSO-LEITE, 2018). However, studies of this nature carried out in urban environments remain scarce, mainly in Brazil (GREGORINI, 2015; GRACIANO-SILVA, MELLO AND CARDOSO-LEITE, 2018;GALVANI, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among the environmental quality assessment methods, one finds the Index of Biotic Integrity (IBI) (MEDEIROS; TOREZAN, 2013), which uses environmental variables such as incidence of indicator species, forest structure, as well as incidence of gaps/dead trees, grass or exotic woody species. Therefore, one can assume that the greater the biotic integrity of a given fragment, the greater its resilience (GRACIANO-SILVA; MELLO; CARDOSO-LEITE, 2018). However, studies of this nature carried out in urban environments remain scarce, mainly in Brazil (GREGORINI, 2015; GRACIANO-SILVA, MELLO AND CARDOSO-LEITE, 2018;GALVANI, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is an increase of the presence of dead trees, clearings, lianas and grasses. These indicators (mainly exotic grasses and dead trees) were present basically in all the studied areas of Sorocaba (Graciano- Silva et al, 2018) and most of them also in Ribeirão Preto (Galvani, 2018). Besides, the occurrence of the "vascular epiphyte" indicator and the absence of "orchids" were also registered for both municipalities, which must be related to the increase of the winds, and the decrease of the relative humidity of the air.…”
Section: Resultsmentioning
confidence: 88%
“…It was calculated the Biotic Integrity Index (BII), proposed by Medeiros and Torezan (2013) and adapted by Graciano- Silva et al, (2018), for each area. It was used 3 plots of 10x10m (or 100 meters square), inside each fragment.…”
Section: Data Collecting Biotic Integrity Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…The applied indices proved to be efficient in the diagnosis of habitat conditions, since they managed to numerically translate the conditions found in the field (Graciano-Silva et al 2018) and directly correlate with the number of species found in the areas. The evaluation of species distribution according to fragment size demonstrates a variation in the distribution of the species abundance according to the size of the areas, with a tendency for larger fragments to maintain a greater number of species.…”
Section: Urban Forest Fragmentsmentioning
confidence: 99%